CXCL16/CXCR6 is involved in LPS‐induced acute lung injury via P38 signalling. Issue 8 (14th June 2019) - Tu, Guo‐wei; Ju, Min‐jie; Zheng, Yi‐jun; Hao, Guang‐wei; Ma, Guo‐guang; Hou, Jun‐yi; Zhang, Xue‐peng; Luo, Zhe; Lu, Li‐ming
Abstract: Although several chemokines play key roles in the pathogenesis of acute lung injury (ALI), the roles of chemokine (C‐X‐C motif) ligand 16 (CXCL16) and its receptor C‐X‐C chemokine receptor type 6 (CXCR6) in ALI pathogenesis remain to be elucidated. The mRNA and protein expression of CXCL16 and CXCR6 was detected after lipopolysaccharide (LPS) stimulation with or without treatment with the nuclear factor‐κB (NF‐κB) inhibitor pyrrolidine dithiocarbamate (PDTC). Lung injury induced by LPS was evaluated in CXCR6 knockout mice. CXCL16 level was elevated in the serum of ALI patients (n = 20) compared with healthy controls (n = 30). CXCL16 treatment (50, 100, and 200 ng/mL) in 16HBE cells significantly decreased the epithelial barrier integrity and E‐cadherin expression, and increased CXCR6 expression, reactive oxygen species (ROS) production, and p38 phosphorylation. Knockdown of CXCR6 or treatment with the p38 inhibitor SB203580 abolished the effects of CXCL16. Moreover, treatment of 16HBE cells with LPS (5, 10, 20 and 50 μg/mL) significantly increased CXCL16 release as well as the mRNA and protein levels of CXCL16 and CXCR6. The effects of LPS treatment (20 μg/mL) were abolished by treatment with PDTC. The results of the luciferase assay further demonstrated that PDTC treatment markedly inhibited the activity of the CXCL16 promoter. In conclusion, CXCL16, whose transcription was enhanced by LPS, may be involved in ROS production, epithelial barrier dysfunction and E‐cadherin down‐regulation via p38 signalling, thus contributing to the pathogenesis of ALI. Importantly, CXCR6 knockout or inhibition of p38 signalling may protect mice from LPS‐induced lung injury by decreasing E‐cadherin expression.